A Teaching System for Hands-on Quadcopter Control. Issue 9 (2019) - Beuchat, Paul N.; Stürz, Yvonne R.; Lygeros, John
Abstract: Quadcopters, popular in consumer and commercial applications, are a perfect testing ground for both basic and advanced control techniques. This makes them an ideal platform for offering experiment-based control courses. We present the software system developed to teach hands-on quadcopter control, that we have used to offer a short course to groups of 32 undergraduate electrical engineering students. Our system allows students to work simultaneously, each with a separate quadcopter. The software makes the hands-on class easy to manage, allowing the instructor to focus on the pedagogic aspects.